Perioperative complications of the right multiport thoracoscopic thymectomy in patients with myasthenia gravis, safeguards, and pitfalls - Amr Abdellateef; Mohammed Keshta; Hatem Elsorogy; Aya Zhran; Yomna M. Yehya; Fetoh Alaaeldin (The Cardiothoracic Surgeon)
Abstract Background While numerous studies have reported the overall safety and efficacy of the multiport video-assisted thoracoscopic (VATS) thymectomy, serious complications are still associated with such a minimally invasive approach. In this series, we try to provide a practical guide to the prevention and management of perioperative complications. This retrospective cohort study represents the experience of a single tertiary referral center from September 2016 to September 2023. The perioperative outcomes of 218 patients who underwent right three-port VATS thymectomy for myasthenia gravis (MG) with special emphasis on operative and postoperative complications were analyzed. Results Intraoperative bleeding occurred in 19 (8.7%) patients, with the highest incidence due to left brachiocephalic vein injury (6.9%). Conversion to open approach was needed in 4 (1.8%) cases due to uncontrollable bleeding. The other 15 bleeding cases were managed thoracoscopically. Operative diaphragmatic injury happened in 7 (3.2%). Two (0.9%) patients experienced intraoperative bradycardia secondary to high CO2 insufflation pressure. Left phrenic nerve palsy with diaphragmatic eventration occurred in 4 patients (1.8%), while two patients (0.9%) suffered from right brachial plexus neuropraxia with temporary upper limb sensory and motor affection. Superficial wound infection and cosmetic female breast dimpling were reported in 12 (5.5%) and 2 (0.9%) patients, respectively. Postoperative re-exploration due to bleeding and hemorrhagic shock was required in one case (0.5%). Eleven patients (5%) experienced early postoperative myasthenic crisis (POMC), from whom 4 patients (1.8%) needed mechanical ventilation. One hospital mortality (0.5%) and another late mortality (0.5%) were recorded. Recurrence of thymoma was reported in 2 (0.9%) patients, 11 and 15 months postoperatively. Conclusions Although some of our reported complications are critical such as intraoperative bleeding and POMC, the incidence of individual complications is still relatively low. Based on this series, we have delineated some of the common pitfalls, identified techniques that minimize complications, and described rescue strategies implemented when complications arise, thereby contributing to lower complication rates and improved perioperative outcomes. Further studies with larger multicenter cohorts and diverse minimally invasive approaches are recommended to determine specific risk factors for individual complications and validate these management strategies across variable approaches.